The impact of leadership style on follower innovation :|mediating effect of idiosyncratic deals - Ünlüaslan Durgun, Esra. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2022., 2022)
This study aims to understand the leader-follower dynamics that lead to higher innovative work behavior. Drawing on social exchange theory, implicit leadership theory, conservation of resources theory and affective events theory, this study investigates the impact of leadership on innovative work behavior through three intertwined models: 1) Leading Innovation in Style: exploring impact of leadership style and cultural values; 2) Leading Innovation through Idiosyncratic Deals: exploring the impact of I-deals and LMXSC; 3) What is a Leader to Give and How Do you Make Me Feel?: exploring the impact of job resources and emotions. Utilizing quantitative data collected from 250 leaders and 250 direct reports sampled from various private sector firms in Turkey, this study demonstrates evidence for the positive effect of both paternalistic and transactional leadership styles on innovative work behavior. The study finds support for a moderated mediation relationship, in which LMXSC positively moderates the relationship of leadership styles and I-deals, which in turn influence innovative work behavior. While mediation holds true for both types of leadership and all types of I-deals, LMXSC moderation is found to be limited to task and work specific I-deals. Lastly, job resources are found to be significant mediators between I-deals and innovative work behavior, and this relationship is moderated by the negative emotions of the follower. Implications of these findings are discussed, as well as the study’s theoretical contributions and practical implications.
Keywords: Leadership.; Leadership -- Study and teaching.; Innovation -- Management.